2019
DOI: 10.1155/2019/8329483
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Psychological Distress among People Living with HIV/AIDS at Selected Hospitals of North Shewa Zone, Amhara Region, Ethiopia

Abstract: Background. The new advances for the treatment of HIV infection using Highly Active Antiretroviral Therapy (HAART) have dramatically improved disease prognosis. However, they are living longer with a chronic condition that increases the risk for psychiatric and psychosocial problems. Various studies have linked HIV/AIDS with a number of psychological problems, depression being the most common. Moreover, studies have found that chronically ill people are at increased risk of psychological problems. Thus, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 25 publications
2
29
3
3
Order By: Relevance
“…5 A study conducted in Amhara, Ethiopia showed that those who felt stigmatized were more likely to develop distress and depression. 7,[28][29][30] A study also indicated that stigma affects access to health care. 31 Some studies have shown that aspects of stigma have been reported as factors constituting a serious obstacle for HIV counseling and testing (VCT) service utilization and HIV prevention.…”
Section: Introductionmentioning
confidence: 99%
“…5 A study conducted in Amhara, Ethiopia showed that those who felt stigmatized were more likely to develop distress and depression. 7,[28][29][30] A study also indicated that stigma affects access to health care. 31 Some studies have shown that aspects of stigma have been reported as factors constituting a serious obstacle for HIV counseling and testing (VCT) service utilization and HIV prevention.…”
Section: Introductionmentioning
confidence: 99%
“…In this systematic review and meta-analysis, we performed a subgroup analysis based on screening tools in which primary studies used to measure CMD. Among a total 13 primary studies included in this review, seven used the Kessler-10 (K-10) [23,[30][31][32][33][34][35], two used the HADS [36,37] and other four used the SRQ-20 [22,29,38,39]. There was a significant difference of CMD reports observed among studies with respect to their screening tools used to measure CMD.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…This result is encouraging in that DSD does not appear to compromise HRQoL and could contribute to an improvement in the emotional wellbeing of patients. This highlights DSD as an acceptable option to explore for HIV care (59)(60)(61)(62). While DSD shows promise in improving acceptability among patients and, therefore, sustainability of such services, our research highlights future research avenues to identify supporting interventions to improve other HRQoL domains among PLHIV.…”
Section: Resultsmentioning
confidence: 84%